Analisis Sosial Ekonomi Penduduk Negeri Suli dalam Kecenderungannya Menjadi Pariwisata Pantai Natsepa di Kecamatan Salahutu Kabupaten Maluku Tengah - Petrus Samaogo Zebua; Melianus Salakory; Wiclif Sepnath Pinoa (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2025)
This study aims to analyze the impact of tourism in Pantai Natsepa on the social and economic conditions of the local community. Using a descriptive quantitative approach, data was collected through interviews, questionnaires, and field observations. The results indicate that tourism has created new business opportunities, increased income, and generated employment. However, most of the community did not experience significant lifestyle changes, and there is a disparity in the involvement of the younger generation. Economic, cultural, and social factors are key drivers of community participation in tourism activities. Awareness of the importance of environmental cleanliness and preservation has increased. The study concludes that tourism has a significant positive impact on the economy, but sustainable management is needed to ensure that the benefits are distributed evenly across the community and to preserve the environment.